FRUIT MATURITY STAGE AND SEED GERMINATION OF THREE SPECIES OF LAURACEAE - HIRANO, Elcio; POSSAMAI, Edilberto (Scientia Agraria, 2008)
The present work had objective to correlate the coloration phases of the fruit with the physiological maturity of the seed, and to verify if seeds of initial phases of fruit presents seed germination. The species used was Ocotea porosa, Ocotea puberula and Ocotea odorifera collected in the area of Canoinhas (SC) in the years of 2002 and 2003. The results showed that the seeds from green fruits may germinate, for Ocotea odorifera must be collected with bellow of 57,3% of seed moisture, for Ocotea porosa bellow of 63,2% and for Ocotea puberula between 34,1% to 40,2% of seed moisture. For the last two species the green fruits presented less insect damage in seeds than ripen and raisin fruits.